Primary cesearean section in multigravidas - Prakash, Sonia Arogya; Vikram, Archana; Gopal K., Raja; Lavanya, Poluri Seeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Cesarean section is one of the widely performed surgical procedures across the world. Cesarean section is associated with increased risk of maternal morbidity and mortality, despite remarkable improvements in the safety. The objective of the present study is to study the cesearean section in the context of various indications, parity, intraoperative complications, post-operative morbidity, and perinatal morbidity among multigravidae undergoing cesarean section for first time. Methods: The present study was carried out at Yenepoya medical college hospital. All multigravidas who had delivered vaginally once or more and who underwent primary caesarean sections for the first time during time period of August 2015-May 2016 were included in study and various factors are analyzed. Results: In our study most of primary cesearean sections were in second paras who constituted 50%, followed by 4/> paras constituting 29.54%, and it was observed that incidence in third paras was 20.45%. 75% of the patients underwent emergency cesearean section and 25% had elective ceserean section. The most common indication for cesearean in our study was observed to be fetal distress accounting for 25% of the cases, 2nd most common being malpresentations (19.31%), non-progress of labor constituting 11.36% of cases. Intra operative complications were noted in 6.81% of cases, most common complication being extension of uterine incision extension of uterine incision. Conclusions: Complications may occur in women who previously had a normal vaginal delivery requiring interventions in the form of caesarean section and is not uncommon. Though to a small extent, they are contributing to rise is total caesarean section rates seen. There are many cases where a caesarean becomes mandatory for her. The fact that a multipara who has had one or more vaginal deliveries should be regarded as an optimistic historical fact, not as diagnostic-criteria for spontaneous delivery of the pregnancy at hand. A parous woman needs good obstetric care to improve maternal and neonatal outcome and still keeping caesarean section to a lower rate.